Grid jobs scheduling improvement using priority rules and backfilling - Azmi, Z. R. M. (Springer Berlin Heidelberg, 2011)
Over the past decade, scheduling in grid computing system has been an active research. However, it is still difficult to find an optimal scheduling algorithm to achieve load balancing. Most of the researchers have focus on schedule-based algorithms such as genetic algorithm and particle swarm optimization to solve this problem and use priority rules algorithms as initial schedule in those algorithms. The main reason this paper was produced is that most of these researchers failed to justify why they use a specific priority rules scheduler as initial schedule in their work. This paper addresses this issue by presenting a comparison results on several priority rules algorithms based on several performance metrics. To add novelty to this paper, we have proposed several schedule-based algorithms that basically based on the combination of backfilling technique and priority rules algorithms. Our results show the significant improvements compared to the original priority rules algorithms.